2015
DOI: 10.2514/1.t4260
|View full text |Cite
|
Sign up to set email alerts
|

Optical Depth Effects on Aluminum Oxide Spectral Emissivity

Abstract: Measurements of high-temperature spectral emissivities of aluminum oxide were made within a heterogeneous shock tube over the spectral range of 650-900 nm. The spectral emissivity of optically thin micrometer-scale alumina particles scaled approximately as λ −1.4 from 2800 to 3500 K. Results from optically thin clouds of nanoscale alumina showed that a λ −1.2 dependence, closer to the λ −1 predicted by the Rayleigh limit, is appropriate over the same spectral and temperature ranges. For temperatures below the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The resulting expression, Equation (8), has the same dependence on wavelength as Equation (4). If the absorptive indexs cales inversely proportional to wavelength, Equation (9) shows that this analysis gives the same emissivity wavelength dependence as Equation (5). This result was also observedf or solid alumina particles [4,5].…”
Section: Particles Of Arbitrary Sizesupporting
confidence: 74%
See 3 more Smart Citations
“…The resulting expression, Equation (8), has the same dependence on wavelength as Equation (4). If the absorptive indexs cales inversely proportional to wavelength, Equation (9) shows that this analysis gives the same emissivity wavelength dependence as Equation (5). This result was also observedf or solid alumina particles [4,5].…”
Section: Particles Of Arbitrary Sizesupporting
confidence: 74%
“…Equations (6)(7)(8)(9) are valid when the complex index of refraction approaches one [14];h owever, some agreement with Mie theory can be seen for aw ider range of the refractive index [16].P lass [16] showed that for materials whose real refractive index is close to one, Equation (8) is ag ood approximation. However,a sn was increased to-wards 2, the approximation is only valid for x 1( for reference, aluminah as ar eal refractive index near 1.7 [4]).…”
Section: Particles Of Arbitrary Sizementioning
confidence: 99%
See 2 more Smart Citations
“…The experimental emission curve is first calibrated to account for the instrument's spectral response prior to comparison with the black body curve. Figure 2 shows an example power law fit (ε∼ −2.94 ) for the relative wavelength dependence of the particles at 1521 K. It was previously shown that the wavelength dependence of the emissivity properties of nano-alumina particles is affected by the phase of the material [13]. A similar effect is expected for micron sized aluminum particles with nanometer thin oxide layers.…”
Section: Experimental Detection Of Melting Point Of Natural Aluminum mentioning
confidence: 55%